THE MEANING OF "WATER" (TIRTA) AS A VISUAL MESSAGE ON “BAK TRUK” IMAGE - Nicholas Wila Adi Pratama (Proceeding Bali-Bhuwana Waskita: Global Art Creativity Conference, 2022)
When examined, the image on “bak truk” is very diverse, both in the type and object of the image. Per the intent and purpose of making images, there are visual expressions and messages. Issues to be discussed are The Meaning of “Water” (Tirta) as a Visual Message in the “Bak Truk” Image. “Argha-Tirtha-Sidhi” (Water Energy and Related Creative Prospects), everything related to the availability and quality of the sea and land water is visualized in “bak truk”. The “Bak truk” image with the theme of “Tirta” has not yet been studied in depth and specifically. This study uses a qualitative methodology in order to be able to capture contextual experiences and obtain data about the phenomenon of the “bak truk” image. They collected literature review data, field data, and direct observation and conducted in-depth interviews with truck owners who participated in the Jogjakarta Truck Festival contest. The selected resource persons include; three actors from members of the freight truck community in different locations (Bali, Padang, Kalimantan) and individuals implementing formal authorities and local informal actors. The “bak truk” image of turning the street into a display case or a demonstration vehicle also colours the public space through the appearance of street art / trans art. This image gives rise to various forms of expression that enliven the traffic atmosphere. Streets can be considered public spaces where various interests are contested.